2019
DOI: 10.1186/s13023-019-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with positive and negative recommendations for cancer and non-cancer drugs for rare diseases in Canada

Abstract: Background In Canada, reimbursement recommendations on drugs for common and rare diseases are overseen by the Canadian Agency for Drugs and Technologies in Health (CADTH) and made through the pan-Canadian Oncology Drug Review (pCODR) and the Common Drug Review (CDR). While the agency specifies information requirements for the review of drug submissions, how that information is used by each process to formulate final reimbursement recommendations, particularly on drugs for rare diseases (DRDs) in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Scholars are divided on drugs of uncertain clinical benefit, with some opposing the positive reimbursement decisions of drugs with unclear clinical benefits ( 21 ) and others advocating that a new standard for drugs with surrogate endpoints should be established ( 22 ). Previous studies have analyzed the relevance between reimbursement decisions and clinical trial endpoints ( 23 28 ), the situation is not consistent across countries, while few studies have focused on the situation in China.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars are divided on drugs of uncertain clinical benefit, with some opposing the positive reimbursement decisions of drugs with unclear clinical benefits ( 21 ) and others advocating that a new standard for drugs with surrogate endpoints should be established ( 22 ). Previous studies have analyzed the relevance between reimbursement decisions and clinical trial endpoints ( 23 28 ), the situation is not consistent across countries, while few studies have focused on the situation in China.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the included studies were shown in Table 1. The majority of studies ( n = 7) (2123;2527;29) only investigated decisions in a single agency, except that Pinto et al (28) study researched the recommendations in two agencies in a separate analysis, and Maynou Pujolras and Cairns (24) study pooled the decisions from six European agencies. A total of six agencies were studied independently, including Pharmaceutical Benefits Advisory Committee (PBAC) in Australia (21), Commission of Reimbursement of Medicines (CRM) in Belgium (27), Health Insurance Review and Assessment Service (HIRA) in South Korea (22), National Authority for Health (HAS) in France (23), NICE in the UK (28), and pCODR in Canada (25;26;28;29).…”
Section: Resultsmentioning
confidence: 99%
“…The number of HTA decisions ranged from 17 to 393 (median = 75). Most studies ( n = 6) have no specific restrictions on the types of cancers with three exceptions that Li et al (23) study was limited to the solid cancers, Niraula and Nugent (26) study was limited to the solid cancers and hematologic malignancies, and Nagase et al (25) study was limited to the rare cancers. The definitions of explored factors and analysis methods were summarized in Supplementary Tables 2 and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed possible influential factors on decision making and found, for example, the reported clinical benefit, level of severity, orphan designation status, study design, treatment intent, and the availability of alternative treatments to influence reimbursement decisions for cancer drugs and drugs in general. 26 , 28 , 31 , 32 , 33 , 34 Concerns regarding the quality of evidence and uncertainty when assessing clinical benefits and effectiveness used in cost-effectiveness analyses and reimbursement decisions have been emphasized. 35 , 36 , 37 Studies on the available evidence for cancer drugs have primarily assessed the evidence used for market authorizations and found that evidence for the clinical benefit is limited regarding the effects on patient-centered outcomes such as survival and QoL.…”
Section: Introductionmentioning
confidence: 99%